Safeguarding the Family from Violence Following a Police Order to Leave or Approach the Apartment - Wolwiak, Ireneusz (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The legislator, aiming to create the broadest possible legal protection for countering the phenomenon of domestic violence, has imposed certain obligations on government administration organs and local government units. A specific scope of this protection was entrusted to the Police authorities, and separate civil proceedings were implemented to obtain judicial protection. The actions of the police – when introducing such a regulation for the first time – will lead to the issuance of an order for the violent offender to leave the premises or a restraining order. The issuance of this administrative act is preceded by certain actions within the framework of the procedure contained in the Police Law, which allows for the determination of the existence of a situation of danger to the life or health of persons affected by violence. This gives rise to the need to analyze the legal regulations contained in various laws for the determination of the normative area of behavior of the participants in these proceedings, while ensuring that the person obliged to vacate the premises or not to approach them, has access to a judicial path. At the same time, the study carried out is intended to make it possible to determine the effectiveness of the protection provided to persons living together with the offender following an order to vacate the premises at the stage of forced execution. The subject of the analysis will finally become the admissibility of extending the protection resulting from the police order for a further period tied to the initiated legal proceedings.